Status of freshwater crayfish (Astacus leptodactylus) in Iran - Karimpour, M.; Harlioglu, M. M.; Aksu, O. (Edp Sciences S A, 2011)
Iranian native crayfish includes one crayfish species, Astacus leptodactylus, with two subspecies, A. l. leptodactylus (lives in freshwater) and A. l. eichwaldi (lives in the Caspian Sea with 12 ppt salinity). Only A. leptodactylus is commonly distributed in Iranian water resources. Nearly 80 years ago local fishermen started to catch Anzali Lagoon crayfish and sold them to foreigners and embassy employees. The consumption of crayfish in Iran is very low, approximately 1 t annually. The first commercially significant crayfish harvest in Iran was 11.3 t from Anzali Lagoon in 1985. It was carried out by a Turkish company. In 1985, the introduction of A. leptodactylus was started into suitable Iranian freshwaters. For example, crayfish from Anzali Lagoon were introduced into Arass water reservoir in 1985. Today, Arass water reservoir is the main resource of crayfish in Iran. There was no further crayfish harvest in Iran until 1993. In that year, a private Iranian company began harvesting the Iranian crayfish and exporting them to European countries. In 1993, 3.2 t of crayfish were exported from Iran. Although there have been fluctuations between years, the export of crayfish in Iran increased remarkably after 1996. The successful results of crayfish introductions gave rise to this increase. In 2003, the export of A. leptodactylus from Iran reached the maximum level (216 t). The commercial value of exported crayfish between 2000 and 2009 varied from 1.5-2.5 million US$ annually and its amount was 106-211.5 t. However, there was a reduction in the export of A. leptodactylus from Iran after 2003, to just above 100 t. In conclusion, in order to increase crayfish production in Iran, introduction of A. leptodactylus into suitable water resources, and management, conservation and monitoring of present crayfish populations should be carried out.
Statut de l'écrevisse à pattes grêles (Astacus leptodactylus) en Iran
Keywords: Astacus leptodactylus; crayfish; distribution; harvest; introduction; Iran